2021
DOI: 10.1016/j.ctro.2021.08.008
|View full text |Cite
|
Sign up to set email alerts
|

PROMIS scores of patients undergoing neoadjuvant and adjuvant radiation therapy for surgically excised soft tissue sarcoma

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Our results are consistent with several prior studies showing worse physical outcomes in AYAs undergoing cancer treatment as compared to the general population 17,19–21 . For patients actively receiving RT, worse physical health could be due to the loss of a normal exercise routine, side effects from RT, or from greater radiation dose distributions to organs that affect physical activity, such as the heart or brain 22–25 . In addition to the burdensome radiation treatment process, impaired physical health may lead to development of comorbidities, work disruptions, or decreased social engagement, which are all significant contributions to morbidity for AYAs 26–29 .…”
Section: Discussionsupporting
confidence: 90%
“…Our results are consistent with several prior studies showing worse physical outcomes in AYAs undergoing cancer treatment as compared to the general population 17,19–21 . For patients actively receiving RT, worse physical health could be due to the loss of a normal exercise routine, side effects from RT, or from greater radiation dose distributions to organs that affect physical activity, such as the heart or brain 22–25 . In addition to the burdensome radiation treatment process, impaired physical health may lead to development of comorbidities, work disruptions, or decreased social engagement, which are all significant contributions to morbidity for AYAs 26–29 .…”
Section: Discussionsupporting
confidence: 90%
“…For example, Chen et al demonstrated that PROMIS scores significantly improved in patients undergoing ACL reconstruction and have the ability to predict postoperative outcomes [ 13 ]. However, the ability of PROMIS to detect differences in patient-reported outcomes in the setting of adult sarcoma has only recently been examined in a small number of studies [ 15 - 16 ]. Additionally, no studies have been performed comparing pre- and postsurgical PROMIS scores in patients with benign versus malignant soft tissue tumors (STTs).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that T-scores are IRT-based scores. Because studies [25][26][27] have reported reliable change in PROMIS using RCI with CTT-based standard errors despite using IRT-based scores, we used the same approach when we applied the CTT method.…”
Section: Discussionmentioning
confidence: 99%